2022
DOI: 10.3390/inventions8010003
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Performance of a Horizontal Axis Wind Turbine Operating with Dust—A Computational Study

Abstract: The main purpose of this study is to develop an understanding of the aerodynamic performance of a horizontal axis wind turbine (HAWT) operating in a dusty environment, with various concentration of dust in the flow domain. The computational analysis was accomplished by the commercial computational fluid dynamics (CFD) code ANSYS Fluent 16.0. Initially, a user-friendly developed application was utilized for the optimum blade geometry special characteristics calculation. The design of the HAWT rotor and meshing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Subsequently, they analyzed the power generation and performance of the HAWT in rainy conditions, and the results indicated that during rain, the pitch angles should be decreased when the wind speed exceeds the predefined threshold value. Douvi et al [117] investigated the aerodynamic characteristics of HAWT with three blades, constructed by NACA 4418 airfoil, under three different rainy conditions. The blade geometry was optimized using the TTBEM application [118], while a commercial CFD code was employed for simulations.…”
Section: Rainfallmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, they analyzed the power generation and performance of the HAWT in rainy conditions, and the results indicated that during rain, the pitch angles should be decreased when the wind speed exceeds the predefined threshold value. Douvi et al [117] investigated the aerodynamic characteristics of HAWT with three blades, constructed by NACA 4418 airfoil, under three different rainy conditions. The blade geometry was optimized using the TTBEM application [118], while a commercial CFD code was employed for simulations.…”
Section: Rainfallmentioning
confidence: 99%
“…The erosion rate resulting from raindrop impact is found to be proportional to the cube of the blade's relative wind velocity, while the impact force exhibits a power-law relationship with the square of the wind velocity. Douvi et al examined, computationally, the impact of hailstorm conditions on the aerodynamic characteristics of the S809 [123] and the NACA 0012 [124] airfoils. The results confirmed that hailstorm conditions have a significant effect on the aerodynamic characteristics of both airfoils, resulting in a decrease in the lift coefficient and an increase in the drag coefficient when compared to normal airflow.…”
Section: Hailstormsmentioning
confidence: 99%
See 1 more Smart Citation
“…Douvi et al [118] investigated the aerodynamic performance of a three-bladed HAWT, with blades constructed by NACA 4418 airfoil, under three different rainy conditions. The blade geometry was optimized using the TTBEM application [119], while a commercial CFD code was employed for simulations.…”
Section: Rainfallmentioning
confidence: 99%
“…Douvi et al examined computationally the impact of hailstorm conditions on the aerodynamic performance of the S809 [124] and the NACA 0012 [125] airfoil. The results confirmed that hailstorm conditions have a significant effect on the aerodynamic performance of both airfoils, resulting in a decrease in the lift coefficient and an increase in the drag coefficient when compared to normal airflow.…”
Section: Hailstormmentioning
confidence: 99%